The impact of maternal hepatitis B virus infection on IVF/ICSI-assisted pregnancy outcomes: a propensity score-matched cohort study - Wenwen Jiang; Suqin Zhu; Rongshan Li; Yan Sun; Xiaojing Chen; Beihong Zheng (Frontiers in Medicine, 2026)
Background Hepatitis B virus (HBV) infection is highly prevalent among women of reproductive age in China, yet whether maternal HBV carrier status affects the outcomes of assisted reproduction remains unclear. Published studies have yielded conflicting results, most were underpowered or inadequately controlled for confounders, and few have tracked outcomes beyond early pregnancy. This study used propensity score matching to evaluate the impact of maternal HBV infection on laboratory, clinical pregnancy, obstetric, and neonatal outcomes in women undergoing their first fresh IVF/ICSI embryo transfer cycle. Methods This retrospective study analyzed clinical data of 3,455 cycles involving couples who underwent fresh IVF/ICSI embryo transfer for the first time at the Reproductive Center of Fujian Maternal and Child Health Hospital from January 2018 to December 2020. Patients were divided into the HBV group ( n = 811) and non-HBV group ( n = 2,644). Propensity score matching was used to perform 1:1 nearest-neighbor matching on baseline covariates, yielding 810 pairs with balanced covariates. Results After propensity score matching, baseline characteristics were well balanced. No significant differences were observed in oocyte maturation rate (52.84% vs. 52.38%), normal fertilization rate (81.73% vs. 82.01%), high-quality embryo rate (57.82% vs. 58.66%), blastocyst formation rate (63.49% vs. 64.45%), implantation rate (30.99% vs. 32.76%), clinical pregnancy rate (44.44% vs. 45.43%), multiple pregnancy rate, miscarriage rate (12.78% vs. 9.24%), stillbirth rate (1.39% vs. 1.09%), ectopic pregnancy rate, or live birth rate (32.59% vs. 32.96%) (all P > 0.05). Rates of gestational hypertension, gestational diabetes, premature rupture of membranes, cesarean delivery, and neonatal outcomes were also comparable. However, the preterm birth rate was higher in the HBV group both before (15.73% vs. 11.10%, P = 0.041) and after matching (15.73% vs. 7.78%, P = 0.004). Conclusions In this propensity score-matched cohort, maternal HBV infection was not associated with impaired laboratory, clinical pregnancy, or live birth outcomes following IVF/ICSI with fresh embryo transfer. Apart from an increased preterm birth rate, no significant differences were observed in obstetric complications or neonatal outcomes. The association with preterm birth warrants further investigation in prospective studies incorporating detailed virologic data.